SPH simulation of hydrodynamic responses for two novel types of silt curtain under combined wave-current conditions - Liu, Xiaodong; Li, Shaowu; Ji, Zezhou; Wu, Qingwei (Applied ocean research, 2021)
Traditional silt curtain is a kind of commonly-used impermeable device for short-term control of suspended solids or turbidity in the water column generated during dredging operations. It is attempted to innovatively apply the silt curtain to more violent hydrodynamic conditions, such as functioning as an isolation structure for preventing sediment transportation into channels and harbor basins in a combined wave and current environment. The Weakly Compressible Smoothed Particle Hydrodynamics (WCSPH) code of Shi and Li et al. (2018), after incorporating an overlapped particle method (OPM), was applied to simulate the responses of a flexible impermeable curtain system as a thin-walled structure fixed to the sea bottom and moving violently under the action of static water pressure heads along and combined with waves. It is found that the modeled results of tensions in the curtain of a Silt Curtain System (SCS) working in emerged mode are in good consistency with the theoretical and experimental results and the SCS in submerged mode would be subject to much smaller tensions than in emerged mode. A large influx rate of q = 0.053 m3/s/m would enhance the wave-induced component of curtain tensions in the submerged mode. When subject to waves, the SCS in emerged mode imposes much more significant influence on wave transmission than in submerged mode, while the SCS in emerged mode produces lower horizontal oscillation ratio than in submerged mode.